Ability tracking and social trust in China's rural secondary school system. Issue 4 (2nd October 2018) - Li, Fan; Loyalka, Prashant; Yi, Hongmei; Shi, Yaojiang; Johnson, Natalie; Rozelle, Scott
ABSTRACT: The goal of this paper is to describe and analyze the relationship between ability tracking and student social trust, in the context of low-income students in developing countries. Drawing on the results from a longitudinal study among 1, 436 low-income students across 132 schools in rural China, we found a significant lack of interpersonal trust and confidence in public institutions among poor rural young adults. We also found that slow-tracked students have a significantly lower level of social trust, comprised of interpersonal trust and confidence in public institutions, relative to their fast-tracked peers. This disparity might further widen the gap between relatively privileged students who stay in school and less privileged students who drop out of school. These results suggest that making high school accessible to more students may improve social trust among rural low-income young adults.